THE ROLE OF STEAM APPROACH AND MIND MAPPING METHOD IN TEACHING NATURAL SCIENCES - Khamidova Zaynura Ramazonovna (Bright Mind Publishing, 2025)
This article explores the role, advantages, and practical application of the widely implemented STEAM approach and mind mapping methodology in modern education, particularly in teaching natural sciences such as biology. The mind mapping technique enhances students' abilities to visualize information, develop branched thinking, creative reasoning, and logical associations. The STEAM approach (Science, Technology, Engineering, Arts, Mathematics) facilitates the effective acquisition of theoretical knowledge through interactive, practical, and creative activities. The article analyzes how complex biological concepts like cell structure, photosynthesis, and DNA replication can be simplified through mind mapping, and provides examples of teaching methods integrating 3D modeling, AR/VR technologies, and artistic tools. Ultimately, the approach fosters deeper student engagement with science, improves understanding, and promotes independent thinking.
Keywords: STEAM, mind mapping, natural sciences, biology, visual learning, 3D modeling, AR/VR technologies, interactive methods, creative thinking, learning process.